Characterization of intestinal microvillar membrane disks: detergent- resistant membrane sheets enriched in associated brush border myosin I (110K-calmodulin) (The Rockefeller University Press, 1989)
The actin bundle within each microvillus of the intestinal brush border (BB) is tethered laterally to the membrane by bridges composed of BB myosin I. Avian BB myosin I, formerly termed 110K-calmodulin, consists of a heavy chain with an apparent Mr of 110 kD and three to four molecules of calmodulin "light chains." Recent studies have shown that this complex shares many properties with myosin including mechanochemical activity. In this report, the isolation and characterization of a membrane fraction enriched in bound BB myosin I is described. This membrane fraction, termed microvillar membrane disks, was purified from ATP extracts of nonionic detergent-treated microvilli prepared from avian intestinal BBs. Ultrastructural analysis revealed that these membranes are flat, disk-shaped sheets with protrusions which are identical in morphology to purified BB myosin I. The disks exhibit actin-activated Mg-ATPase activity and bind and cross- link actin filaments in an ATP-dependent fashion. The mechanochemical activity of the membrane disks was assessed using the Nitella bead movement assay (Sheetz, M. P., and J. A. Spudich. 1983. Nature [Lond.]. 303:31-35). These preparations were shown to be free of significant contamination by conventional BB myosin. Latex beads coated with microvillar membrane disks move in a myosin-like fashion along Nitella actin cables at rates of 12-60 nm/s (average rate of 33 nm/s); unlike purified BB myosin I, the movement of membrane disk-coated beads was most reproducibly observed in buffers containing low Ca2+.